Efficacy of arthrocentesis with injection of hyaluronic acid in the treatment of inflammatory-degenerative disease of temporomandibular joint - Enas A Abdulmaged; Thair Abdul Lateef (College of Dentistry/ University of Baghdad, 2021)
Background:Temporomandibular joint (TMJ) problems refer to a group of heterogeneous pain and dysfunction conditions involving the mastication, reducing life quality of the patients. Arthrocentesis is a simple and less invasive surgical method for the treatment of inflammatory-degenerative disease than other conservative procedures and better than arthroscope. This clinical study aimed at evaluating the benefit of arthrocentesis with injection of hyaluronic acid in the management of inflammatory-degenerative disease of the TMJ. Material and methods: Eighty consecutive patients were enrolled in this study with pain symptoms of TMJ, insufficient masticatory efficiency during function and limitation of mouth opening; they were assessed with clinical examination and approved with computed tomography scan. Arthrocentesis was done by inserting 18 gauge needles in the upper joint compartment, lavage by normal saline solution and at the end of the procedure 1ml of hyaluronic acid (HA) was injected. Intensity of the TMJ pain and masticatory efficiency was analyzed by visual analog scale (VAS), maximum mouth opening (MMO) was assessed by a ruler. All the assessed parameters were measured before the procedure then 1 and 4 months later. Results: During 5 months follow-up, comparison of the obtained results showed reduction in pain at chewing and rest 87.5%, improvement in mouth opening 100% and significant improvement in masticatory efficiency 87.5% of patients. Conclusion: The procedure of arthrocentesis with Sodium Hyaluronate injection, used in patients who suffered from inflammatory-degenerative disease (IDD), showed therapeutic benefits, simplicity, safety, patient satisfaction, lack of significant side effects and complications.